Spatio-temporal accessibility to public transport and nighttime leisure: a case study of youth in Alcobendas - Roca-Medina, Andrés; Moreno-Jiménez, Antonio (Revista de Estudios Andaluces, 2022)
Within the framework of current research on intra-urban accessibility, this study aims to characterize the access of young population to the public transport network for night-time leisure, as well as to identify the inequalities, and potential socio-spatial inequities in the city of Alcobendas (Autonomous Community of Madrid, Spain). As to methods, we have resorted, among others, to the General Transit Feed Specification data, which provide innovative analytical opportunities, and to the Geographic Information Systems processing and inferential statistical techniques. The results reveal, with high temporal and spatial accuracy, a broad coverage of this population group, prioritizing the areas with the highest potential demand and the lowest per capita income, although they also uncover some problems in certain night-time periods and areas, particularly in terms of frequency.